2014
DOI: 10.1021/cm404062r
|View full text |Cite
|
Sign up to set email alerts
|

Methane Decomposition and Carbon Growth on Y2O3, Yttria-Stabilized Zirconia, and ZrO2

Abstract: Carbon deposition following thermal methane decomposition under dry and steam reforming conditions has been studied on yttria-stabilized zirconia (YSZ), Y2O3, and ZrO2 by a range of different chemical, structural, and spectroscopic characterization techniques, including aberration-corrected electron microscopy, Raman spectroscopy, electric impedance spectroscopy, and volumetric adsorption techniques. Concordantly, all experimental techniques reveal the formation of a conducting layer of disordered nanocrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 47 publications
6
87
0
1
Order By: Relevance
“…5b. Kogler et al 45 also concluded in their experimental study that methane dissociation is possible on pure YSZ oxides, which efficiently promotes methane-induced growth of different carbon species. Amorphous carbon was identified as a dark layer without a clear structure, which covered the anode surface.…”
Section: Resultsmentioning
confidence: 96%
“…5b. Kogler et al 45 also concluded in their experimental study that methane dissociation is possible on pure YSZ oxides, which efficiently promotes methane-induced growth of different carbon species. Amorphous carbon was identified as a dark layer without a clear structure, which covered the anode surface.…”
Section: Resultsmentioning
confidence: 96%
“…Even though completely different mechanisms are taking place, e.g., on CH 4 oxide-specific H abstraction from methane by active surface entities capable of binding H 2 in combination with gas-phase radical reactions at T > 1000 K takes place, 17,19 whereas for CO, the inverse Boudouard reaction, which is likely mediated by surface-reduced centers/oxygen vacancies, is responsible for the low final impedance value.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon deposition is visible starting at T > 1023 K (Figure 2, drop of the total transmittance). Especially at higher temperatures ( T > 1173 K)—as in methane 17 —the transmittance drops to zero while the impedance reaches ohmic resistance, caused by a conducting carbon layer. At lower temperatures ( T < 1173 K) the surface chemistry is dominated by formate formation (br-formate: ν as (OCO) = 1595 cm –1 , δ(CH) = 1382 cm –1 , ν s (OCO) = 1332 cm –1 , ν(CH) = 2856 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations